2018
DOI: 10.1164/rccm.201710-2033oc
|View full text |Cite
|
Sign up to set email alerts
|

Chronic E-Cigarette Exposure Alters the Human Bronchial Epithelial Proteome

Abstract: We conclude that chronic vaping exerts marked biological effects on the lung and that these effects may in part be mediated by the PG/VG base. These changes are likely not harmless and may have clinical implications for the development of chronic lung disease. Further studies will be required to determine the full extent of vaping on the lung.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
152
2
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(195 citation statements)
references
References 55 publications
15
152
2
7
Order By: Relevance
“…However, we demonstrate that although nicotine may affect cellular responses, PG/VG alone can modulate both pulmonary lipid homeostasis and local innate immune cell function. This corroborates the work of others in the field who have demonstrated molecular changes in human lung tissue in response to vehicle solvents alone (51,52). In response to long-term exposure to ENDS, we reveal a distinct impairment in lung macrophage immune function.…”
Section: Discussionsupporting
confidence: 92%
“…However, we demonstrate that although nicotine may affect cellular responses, PG/VG alone can modulate both pulmonary lipid homeostasis and local innate immune cell function. This corroborates the work of others in the field who have demonstrated molecular changes in human lung tissue in response to vehicle solvents alone (51,52). In response to long-term exposure to ENDS, we reveal a distinct impairment in lung macrophage immune function.…”
Section: Discussionsupporting
confidence: 92%
“…Both chronic CS and E‐cigarette users had more erythematous and irritable airway mucosa, and there were approximately 200 proteins altered (78 proteins altered in both groups and 113 specifically altered in vapers) in bronchial epithelium, including mucin MUC5AC that facilitates mucus secretion. Of note, some proteins up‐regulated in vapers like MUC5AC, CYP1B (generates covalent adducts to damage DNA) and STIM1 (controls Ca 2+ homeostasis) were also elevated by aerosolized PG/VG in HBECs in vitro . Aside from direct use, a 30‐minute passive exposure to E‐cigarette vapour in healthy non‐smokers caused small airway irritation and inflammation detected by increased resonant frequency and reduced FeNO, raising the possibility of potential risk to humans exposed to ECV in public places and environments …”
Section: Effects Of E‐cigarettes In Humansmentioning
confidence: 99%
“…Of note, some proteins up-regulated in vapers like MUC5AC, CYP1B (generates covalent adducts to damage DNA) and STIM1 (controls Ca 2+ homeostasis) were also elevated by aerosolized PG/VG in HBECs in vitro. 54 Aside from direct use, a 30-minute passive exposure to E-cigarette vapour in healthy non-smokers caused small airway irritation and inflammation detected by increased resonant frequency and reduced FeNO, raising the possibility of potential risk to humans exposed to ECV in public places and environments. 55 Overall, the studies considered here indicate that ECV is less deleterious to the respiratory system than CS, but still has significant toxic and inflammatory effects whose longterm consequences are currently unknown.…”
Section: Effects Of E-cigarettes On the Respiratory Systemmentioning
confidence: 99%
“…E-cigs deliver an aerosol (known as vapor) from e-liquids that can contain propylene glycol (PG), vegetable glycerol (VG), flavors and nicotine in different concentrations and ratios [17]. Although the percentage of toxic compounds found in e-cig vapor (e-vapor) are lower than cigarette smoke [17], some studies have shown a toxic effect on cells like alveolar macrophages [18], lung epithelial cells [19][20][21][22] and monocytic cells [23] as well as proteomic changes in the cells of the lower airways [24] and pro-inflammatory response [19,21,23,25]. Moreover, function damage in macrophages has been observed and therefore an enhancement of infections caused by microorganisms such as Haemophilus influenzae [26], Escherichia coli [18], Staphylococcus aureus [18,21] and Streptococcus pneumoniae [27].…”
Section: Introductionmentioning
confidence: 99%